Follow up and close the sale : make easy (and effective) follow-up your winning habit - Shore, Jeff, 1962- (McGraw-Hill, 2020)
"Award-winning sales coach Jeff Shore shows sales professionals how to apply buyer psychology to personalize follow-ups, serve customers-and seal the deal faster. What does a sales professional do when the customer says, "Not yet"? Companies have invested thousands and even millions of dollars in CRM technology over the past decade, but frontline salespeople and sales executives alike are still groping for solutions. The problem of drift-a common phenomenon in which a prospect simply forgets about the product offering and goes dark-is persistent and rampant. Technology doesn't change behavior on its own. Behavior is changed by adopting better habits. The fact is 44 percent of salespeople give up after one follow-up attempt. That sad reality presents a genuine opportunity. In Follow Up and Close the Sale, Jeff Shore offers research-based insights into the customer's buying journey to teach sales professionals how to: Create and maintain Emotional Altitude for the customer Leverage speed as an advantage Personalize follow-up to fulfill customer needs and provide value Overcome the mental barriers that make follow-up a difficult task Select the right follow-up method Stay in touch without annoying the prospect "Wake up" tired leads Better yet, this results-oriented book will make the follow-up process, one often dreaded as a grueling chore, to be genuinely enjoyable. Effective follow-up is relationship-based, service-driven, and emotionally positive. It's about rituals and routines, rhythms and the right attitude. It's about quitting when others give up. Follow-up is what separates the good from the great"--